Reduced‐bandgap triphenylamine‐alt‐benzo[1, 2‐b:4, 5‐b′]dithiophene copolymers pending benzothiadiazole or diketopyrrolopyrrole units for efficient polymer solar cells. Issue 19 (2nd July 2013) - Nie, Kaixuan; Tan, Hua; Deng, Xianping; Wang, Yafei; Chen, Qing; Huang, Ying; Liu, Yu; Yang, Chuncheng; Huang, Zhenrong; Zhu, Meixiang; Zhu, Weiguo
ABSTRACT Two new side‐chain donor–acceptor (D‐A)‐based triphenylamine‐alt‐benzo[1, 2‐b:4, 5‐b′]dithiophene (TPA‐alt‐BDT) copolymers (P1 and P2) with pendant benzothiadiazole (BT)/diketopyrrolopyrrole (DPP) in TPA unit were synthesized by Stille coupling polymerization. Their thermal, photophysical, electrochemical, blend film morphology and photovoltaic properties were investigated. Efficient bulk heterojunction polymer solar cells (PSCs) were obtained by solution process using both copolymers as donor materials and PC71BM as acceptor. The maximum power conversion efficiency (PCE) of 3.17% with a highest open‐circuit voltage (Voc) of 0.86V was observed in the P1‐based PSCs, while the maximum short‐circuit current (Jsc) of 10.77 mA cm−2 was exhibited in the P2‐based PSCs under the illumination of AM 1.5, 100 mW cm−2. The alternating binary donor units and pending acceptor groups played a significant role in tuning photovoltaic properties for this class of the side‐chain D–A‐based copolymers. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4103–4110